The Baghdad blog - Salam Pax (Atlantic on behalf of Guardian Newspapers, 2003)
This volume collects together Salam Pax's writings to tell the story of the war in Iraq from inside that besieged country. It provides a gripping perspective on the conflict and its aftermath.